مسؤولية الناقل البحري في التشريع الجزائري - رفيقة طوبال (My University, 2022)
Summary: The maritime carrier's liability is a civil liability based on the availability of its three pillars. It is the fault, the damage and the causal link between the fault and the damage, which, on the occasion of the carrier's breach of its contractual obligation, is of a contractual nature arising from the contract of carriage by sea from the port of shipment to the port of arrival, The carrier's obligation is to achieve a result and, if the result is not verified, the fault is presumed by the carrier. This presumed error is capable of proving the contrary, and if the maritime carrier breaches its obligations to transport and deliver the goods to the consignee as codified in the shipping document, the shipping carrier is liable and thus held accountable for the breach. The arrival of goods is improper for the stakeholder to be held accountable by the maritime carrier which gives the injured party the right to liability of the maritime carrier and the shipper or consignee may be a means of obtaining its right as a result of a breach of its contractual obligations by bringing the claim of liability of the maritime carrier in order to obtain compensation in accordance with established legal procedures, However, damages may be substantial and burdensome for the carrier, making Algerian legislation a legal limitation of the carrier's liability by mitigating the impact of such damages on the maritime carrier and Algerian legislation has also allocated cases in which the maritime carrier is exempted from such liability. ................. ملخص: إن مسؤولية الناقل البحري هي مسؤولية مدنية تقوم بتوافر أركانها الثلاث. وهي الخطأ، الضرر والعلاقة السببية بين الخطأ والضرر، إذ تقوم بمناسبة إخلال الناقل بالتزامه التعاقدي فهي ذات طبيعة عقدية ناشئة عن عقد النقل البحري، والمتمثل في إيصال البضاعة سالمة من ميناء الشحن إلى ميناء الوصول، والتزام الناقل هو التزام بتحقيق نتيجة، وفي حالة عدم التحقق من النتيجة فإن الخطأ يفترض من جانب الناقل، وهذا الخطأ المفترض قابل لإثبات العكس، فإذا أخل الناقل البحري بالتزاماته والمتمثلة في نقل البضاعة وتسليمها إلى المرسل إليه سليمة كما هي مدونة في وثيقة الشحن قامت مسؤولية الناقل البحري وبالتالي مساءلته عن هذا الإخلال. فوصول البضاعة غير سليمة إلى صاحب المصلحة يعرض الناقل البحري لمساءلته، مما يعطي الحق للطرف المضرور في مسؤولية الناقل البحري والذي قد يكون الشاحن أو المرسل إليه وسيلة للحصول على حقه نتيجة لإخلاله بالتزاماته التعاقدية وذلك عن طريق رفع دعوى مسؤولية الناقل البحري من أجل الحصول على التعويض وفقا لإجراءات قانونية متبعة، غير أن التعويضات قد تكون ضخمة وعبء على الناقل مما جعل التشريع الجزائري يضع تحديد قانوني لمسؤولية الناقل يخفف من خلاله أثر هذه التعويضات على الناقل البحري، كما خصص التشريع الجزائري الحالات التي يعفى منها الناقل البحري من هذه المسؤولية. ...................... Résumé : La responsabilité du transporteur maritime est une responsabilité civile fondée sur la disponibilité de ses trois piliers. C’est la faute, le dommage et le lien de causalité entre la faute et le dommage qui, à l’occasion de la violation par le transporteur de son obligation contractuelle, est de nature contractuelle découlant du contrat de transport par mer du port d’expédition au port d’arrivée, L’obligation du transporteur est d’obtenir un résultat et, si le résultat n’est pas vérifié, la faute est présumée par le transporteur. Cette erreur présumée est susceptible de prouver le contraire, et si le transporteur maritime viole ses obligations de transport et de livraison des marchandises au destinataire telles que codifiées dans le document d’expédition, le transporteur maritime est responsable et donc tenu responsable de la violation. L’arrivée de marchandises est inappropriée pour l’intervenant d’être tenu responsable par le transporteur maritime qui donne à la partie lésée le droit à la responsabilité du transporteur maritime et l’expéditeur ou le destinataire peut être un moyen d’obtenir son droit en raison d’une violation de son les obligations contractuelles en invoquant la responsabilité du transporteur maritime afin d’obtenir une indemnisation conformément aux procédures légales établies, Toutefois, les dommages peuvent être importants